2011
DOI: 10.1111/j.1447-0349.2011.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

An emergency department-based mental health nurse practitioner outpatient service: Part 1, participant evaluation

Abstract: The mental health liaison nurse role in the emergency department (ED) has demonstrated a range of positive outcomes for both consumers and staff. In Australia, the added value associated with establishing mental health nurse practitioner (MHNP) positions based on this model is emerging. This paper presents qualitative findings from a study using a mixed-method design to evaluate an ED-based MHNP outpatient service in Sydney, Australia. In evaluating this new service, semistructured interviews were conducted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…Initial evaluations of the service provided by the MHNP identified reduced waiting times, therapeutic engagement and enhanced co-ordination of care as the main benefits of the role (Wand, 2004;Wand and Schaecken, 2006). The scope of the MHNP role at RPAH has expanded through the establishment of a structured and formalised outpatient service (Wand et al, 2011a(Wand et al, , 2011b(Wand et al, , 2012 whereby referred patients return to the ED for brief intervention within a mental health promotion and solution focused therapy framework.…”
Section: The Rpah Contextmentioning
confidence: 98%
“…Initial evaluations of the service provided by the MHNP identified reduced waiting times, therapeutic engagement and enhanced co-ordination of care as the main benefits of the role (Wand, 2004;Wand and Schaecken, 2006). The scope of the MHNP role at RPAH has expanded through the establishment of a structured and formalised outpatient service (Wand et al, 2011a(Wand et al, , 2011b(Wand et al, , 2012 whereby referred patients return to the ED for brief intervention within a mental health promotion and solution focused therapy framework.…”
Section: The Rpah Contextmentioning
confidence: 98%
“…[99][100][101] There was limited evidence of benefit in two Australian studies based on a limited range of outcomes but neither of these was a controlled trial. McDonough et al 99 found a reduction in mean waiting time (before, 235 minutes; after, 36 minutes) and an increase in nightly service user contact rate (before, 2.9; after, 3.75).…”
mentioning
confidence: 99%
“…McDonough et al 99 found a reduction in mean waiting time (before, 235 minutes; after, 36 minutes) and an increase in nightly service user contact rate (before, 2.9; after, 3.75). A mixed-methods study by Wand et al 101 found largely positive feedback about the psychiatric nursing service in the ED, but there was no control group so it was difficult to determine the impact of the intervention.…”
mentioning
confidence: 99%
“…Realistic evaluation (Pawson & Tilley, 1997), the methodology applied to this project, and the three phase process involved in developing and implementing the MHNP outpatient service (including structure and procedural considerations) has been detailed by the authors previously (Wand, White, & Patching, 2010a; Wand, White, Patching, Dixon, & Green, 2010). Realistic evaluation is a practical adaptation of critical realist philosophy and draws on a range of methods in order to understand how individuals respond to an intervention or program.…”
Section: Study Aimsmentioning
confidence: 99%